EFEK MODERASI KEPEMIMPINAN PADA PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KEPUASAN KERJA - -, Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
ABSTRACT This study aims to analyze (1) effect leadership towards the performance of lecturers and employee’s; (2) role of leadership as a moderator of the influences employee engagement towards job satisfaction of lecturers and employee’s. Sample are 78 lecturers and employee’s from all faculties in area of Slamet Riyadi University on Surakarta, taken by proportional sampling technique. To test the hypothesis, the researcher uses Regression Moderated Analysis, meanwhile to process the data, the SPSS Release 12 program is used. Results of t-test indicate that (1) employee engagement has a significantly effect to job satisfaction of lecturers and employee’s. This is indicated by t test with p value (0,006) < 0,05, thus supporting hypothesis 1; (2) leadership moderate the influence of employee engagement on job satisfaction of lecturers and employee’s. This is indicated by t test with p value (0,010) < 0,05, thus supporting hypothesis 2. Keywords: employee engagement, leadership, job satisfaction.